PERSEPSI GURU TERHADAP PEMBELAJARAN SOSIO-KULTURAL UNTUK ANAK USIA DINI DI TK PUSAT PAUD HARAPAN BANGSA PARANG LOE, GOWA-SULAWESI SELATAN - Hafisah; Mutiara; Carmelita Patrisia Due; Hajerah; Muhammad Akil Musi (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2026)
The implementation of socio-cultural learning in early childhood education has not been fully optimal due to the influence of differences in children's social characteristics, the lack of local culture-based learning media, limited learning time, and the lack of teacher training on socio-cultural approaches. The purpose of this research was to describe teachers' perceptions of socio-cultural learning at Harapan Bangsa Kindergarten, PAUD Pusat. This research used qualitative techniques with a descriptive approach to gain an understanding of teachers' perceptions, learning implementation, children's social interactions, and supporting and inhibiting factors for learning. The subjects of the study were two class teachers directly involved in early childhood learning activities. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that teachers had a positive perception of socio-cultural learning because it was able to support children's social development through habits of cooperation, sharing, the use of polite language, and the integration of local culture into daily learning. The implementation of learning was carried out through group play, role-playing, storytelling, singing, and cooperation. This learning had a positive influence on communication skills, social interactions, empathy, self-confidence, and an attitude of respect for children's socio-cultural context. Thus, socio-cultural learning is an effective way that can help social development and character formation from an early age in a contextual, collaborative, and sustainable manner.